H2 evolution on Lanthanum and Carbon co-doped NaTaO3 Photocatalyst - Husni Husin; Mahidin Mahidin; Zuhra Zuhra; Fikri Hafita (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2014)
We report a carbon-modify lanthanum doped sodium tantalum oxide powders (La-C-NaTaO3) by sol-gel process. The resultant materials are characterized by powder X-ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). The X ray diffraction of La-C-NaTaO3 show a single phases with a good crystallinity and without any impurity. The samples is exactly indexed as NaTaO3 monoclinic structure with the space group P2/m. The SEM measurements give a smaller particle size of doped NaTaO3 than pure NaTaO3. The effect of dopant on the photocatalytic activity of La-C-NaTaO3 in the photocatalytic of hydrogen generation is studied and compared with pure NaTaO3. The results show that the rate of hydrogen evolution over La-C-NaTaO3 is higher as compared to that of pure NaTaO3. The enhancement of photocatalytic activity of La-C-NaTaO3 nanocrystalline is mainly due to their capability for reducing the electron hole pair recombination. The La-C-dopant is believed to play a key role in the enhancement of photocatalytic properties of La-C-NaTaO3 crystalline. © 2014 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)